1997
DOI: 10.2527/1997.752483x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen concentration and free radicals on in vitro development of in vitro-produced bovine embryos.

Abstract: The effects of free radicals and hypotaurine on the development of bovine embryos produced by in vitro fertilization of in vitro-matured oocytes were examined. Embryos that developed to the 4- to 6-cell stage after in vitro fertilization were cultured without feeder cells in TCM199 medium supplemented with 1% calf serum (CS) under either 5% CO2 in air or 5% O2, 5% CO2 and 90% N2. The percentages of blastocysts (including early, expanding, and hatched stages) that developed under 5% O2 was higher (P < .01) than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
56
1
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 27 publications
3
56
1
4
Order By: Relevance
“…Therefore, IGF-I may promote embryonic development by an anti-apoptotic effect instead of increasing HIF-1α expression. Embryos cultured in vitro under low (5 %) oxygen tension have been reported to show higher developmental rates than those cultured under 20 % oxygen in mice [43], cattle [44], and human [23]. These reports indicated that a high oxygen tension during in vitro culture was found to be toxic to mammalian embryos, probably due to the formation of reactive oxygen species (ROS) [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, IGF-I may promote embryonic development by an anti-apoptotic effect instead of increasing HIF-1α expression. Embryos cultured in vitro under low (5 %) oxygen tension have been reported to show higher developmental rates than those cultured under 20 % oxygen in mice [43], cattle [44], and human [23]. These reports indicated that a high oxygen tension during in vitro culture was found to be toxic to mammalian embryos, probably due to the formation of reactive oxygen species (ROS) [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Liu and Foote [14] showed that the inclusion of 7 or 14 mM taurine improved the development of 4-to 8-cell bovine embryos to the blastocyst stage after 6 days of culture in 20% O 2 , but that taurine was not beneficial in 5% O 2 . Most recently, Fujitani et al [8] reported that the addition of 10 mM hypotaurine to TCM199 supplemented with 1% calf serum increased the cell number in the blastocyst, although hypotaurine did not improve the percentage of bovine 4-to 6-cell embryos that developed to the blastocyst stage. In the present experiment, the addition of 2 or 10 mM taurine enhanced the development of zygotes to blastocysts even in a gas atmosphere with 5% O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Taurine, serving as an oxidant or an oxygen radical scavenger, has been found to counteract the negative effect of 20% O 2 , but the addition of taurine was not beneficial under 5% O 2 on the development of bovine 4-to 8-cell embryos [14]. The addition of hypotaurine, which is the precursor of taurine, has recently been reported to improve bovine embryonic development even under 5% O 2 [8]. The effect of taurine is still obscure, and needs to be determined.…”
mentioning
confidence: 99%
“…performed using a small number of sperm, it takes a much longer time until sperm injection, causing the accumulation of reactive oxygen species [3,4]. Such changes in culture conditions have been shown to be involved in the lipid peroxidation of cell membranes, nuclear DNA fragmentation, and delay of embryo development [5][6][7][8]. Several groups have reported the cryopreservation of a small number of sperm using devices for embryo vitrification [9,10] by embedding them into an alginate gel [11] and by injecting them into an empty zona pellucida (ZP) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%